The Effect of Using Coloring Activities on the Concentration and Fine Motor Skills of Kindergarten B Students at Al Muhajir Islamic Kindergarten - Nameira Kayla Yukitami; Pratidina Ekanesia; Rifqi Farisan Akbar (International Journal of Marketing & Human Resource Research, 2026)
This research examined whether structured coloring activities could strengthen learning concentration and fine motor performance among Kindergarten B children at Al Muhajir Islamic Kindergarten, Bandung. A one-group pretest-posttest design was applied to 25 children aged 6–7 years who joined the school’s extracurricular coloring program. Data were obtained through a 24-item observation instrument covering concentration and fine motor indicators. Instrument testing showed that every item met the validity criterion, with item correlations exceeding the critical value of 0.396. The scales also demonstrated very high internal consistency, with Cronbach’s alpha coefficients of 0.976 for concentration and 0.972 for fine motor skills. Shapiro-Wilk testing confirmed that the score differences were normally distributed, allowing the use of paired-samples t-tests. The findings revealed a statistically significant rise in concentration, with the mean score increasing from 35.04 before the activity to 38.48 afterward, p = .039. In contrast, the change in fine motor performance was not statistically significant, p = .373. These findings suggest that structured coloring can be used to support children’s attention during learning activities, although a brief intervention may not be sufficient to generate measurable improvement in fine motor development.